Mary Edwards Bryan : Her Early Life and Works - Brown, Canter, Jr., 1948-; Rivers, Larry E., 1950- (Book collections on Project MUSE., 2015)
Mary Edwards Bryan, a Victorian-era southern woman, was an influential and well-respected writer during her time. Brown and Rivers hope to reintroduce her to the world with this "literary" biography --